HISTOMORPHOMETRY OF THE SUPERFICIAL PECTORALIS MUSCULAR AND CRANIAL TIBIALIS MUSCULAR OF BALI DUCKS IN THE GROWTH PHASE - I Kadek Ari Satria Prayoga; Ni Luh Eka Setiasih; Luh Gde Sri Surya Heryani; Ni Ketut Suwiti; Ni Nyoman Werdi Susari; I Ketut Suatha (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Superficial pectoralis muscle is a chest muscle that is located on the surface and functions in wing movement. Tibialis cranialis muscle is the top muscle in the calf muscle structure, which functions to support the bird's body. This study aims to determine the histomorphometry of the superficial pectoralis muscle and cranial tibial muscle of male and female Bali ducks in the growing phase. This research used 20 Balinese ducks aged 12 weeks. Direct anatomical examination and histological structure with a binocular light microscope. Histomorphometry was measured using the Olympus Cellsens Standard application. Anatomy and histology results were analyzed using descriptive qualitative analysis, and histomorphometry using the ANOVA test with mean estimation. Histological structure of the superficial pectoralis muscle and cranial tibial muscle consists of muscle fibers, fasciculus, endomysium, perimysium and epimysium connective tissue. Histomorphometry of fascicle size, perimysium connective tissue thickness, and superficial pectoralis muscle endomysium were significantly different (P<0.05). Histomorphometry of the size of the fasciculus, perimysium connective tissue and endomysium of the cranial tibial muscle was not significantly different (P>0.05) in different genders. It can be concluded that the superficial pectoralis muscle and cranial tibial muscle of males and females in the growing phase are the same in terms of anatomical structure, but the size of the histological structure is different. Histomorphometry of the superficial pectoralis muscle of male and female Bali ducks is significantly different (P<0.05), but not for the tibialis cranialis muscle. Further research is needed regarding the muscles of Bali ducks at other ages.